Roles of surface and bulk states in giant magnetoresistance and anomalous hall effect in antiferromagnetically ordered Bi1.9Dy0.1Te3 topological insulators - Gangwar V.K.; Kumar S.; Singh M.; Pal D.; Ghosh L.; Singh P.; Yufeng Z.; Chen C.; Schwier E.F.; Shimada K.; Shahi P.; Uwatoko Y.; Patil S.; Ghosh A.K.; Chatterjee S. (My University, 2025)
A wide variety of emerging spintronic device concepts will greatly benefit from the use of materials with an anomalous Hall effect and large magnetoresistance. In this regard, a magnetic topological insulator is a potential candidate, leading to a better way to manipulate spin. The different roles of surface and bulk states in Bi1.9Dy0.1Te3 topological insulators are determined by investigating electronic states, magnetotransport properties, Seebeck coefficient and magnetization. Magnetoresistance attains a huge value ∼1500% at a magnetic field of 7 T, which is attributed to the surface state. The magnetization behavior clearly suggests the existence of an antiferromagnetic state. The observed anomalous Hall effect is established as the contribution from the bulk state. Furthermore, it is demonstrated that there is no appreciable energy gap at the Dirac point of the topological surface. © 2022 The Royal Society of Chemistry.